2022
DOI: 10.1007/s10973-022-11728-3
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the activation energy under isothermal conditions: revisited

Abstract: The kinetic analysis of solid-state processes aims at obtaining fundamental information that can be used for predicting the time evolution of a process within a wide range of conditions. It is an extended belief that the determination of the kinetic parameters from the analysis of curves recorded under isothermal conditions is strongly conditioned by the kinetic model used to fit the experimental data. Thus, much effort is devoted to finding the model that truly describes a process in order to calculate the ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
2
5
0
Order By: Relevance
“…The error was less than 1% between the two methods. These results are largely consistent with the references [46,47].…”
Section: Kinetic Analysissupporting
confidence: 93%
See 2 more Smart Citations
“…The error was less than 1% between the two methods. These results are largely consistent with the references [46,47].…”
Section: Kinetic Analysissupporting
confidence: 93%
“…These results are largely consistent with the references [47,48]. Figure 5 shows the relationship between ln(β/Tp 2 ) and 1000/T, as well as that between ln(β/Tp) and 1000/T, according to the Kissinger [29] and Augis-Bennett/Boswell methods [45,46], respectively, for determination of the activation energy. Both methods gave approximately equal results within the permissible error.…”
Section: Kinetic Analysissupporting
confidence: 87%
See 1 more Smart Citation
“…It is important to mention that the data acquired from the X52 steel indicated the presence of a nonlinear profile, where minor CR values corresponded to high activation energies in the range of 17.0 kJ/mol to 27.7 kJ/mol under flowing media, which were determined from the slopes. When the CR is involved in the activation energy, then the following analysis is taken into consideration [13,43,[45][46][47]:…”
Section: Polarization Curvesmentioning
confidence: 99%
“…When CR is low, then Ea is high; thus, a physisorption is considered. This is indicative to a profound impact on the internal corrosion on X60 and X70 steels exposed to OPW so salty and acidic sour solution because a minimum quantity of Ea should be required to start a rate of the steel dissolution as a result of an initial electrochemical deterioration [45][46][47]. It was reported that the result of Ea obtained from X65 steel exposed to acidic solution was around 21.08 kJ/mol [48].…”
Section: Polarization Curvesmentioning
confidence: 99%